The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2001
DOI: 10.1007/s11627-001-0024-z
|View full text |Cite
|
Sign up to set email alerts
|

Phosphomannose isomerase: An efficient selectable marker for plant transformation

Abstract: Phosphomannose isomerase (PMI) catalyzes the reversible interconversion of mannose 6-phosphate and fructose 6-phosphate. Plant cells lacking this enzyme are incapable of surviving on synthetic medium containing mannose as a carbon source. Maize, wheat and barley plants, genetically modified to express the Escherichia coli manA gene (pmi) under the control of a plant promoter, were able to survive selection on mannose-containing medium. Transformation frequencies averaged 45% for maize transformation via Biolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(62 citation statements)
references
References 29 publications
(23 reference statements)
1
61
0
Order By: Relevance
“…Therefore, these two proteins bear no similarity to known allergenic proteins and the preliminary but not conclusive statement is that they do not represent a risk for allergenicity. Our results are similar to the results reported for PMI by Reed et al (54) and are an endorsement for the wide use of the gene for PMI as a selectable marker in plant genetic transformation.…”
Section: Allergenicity Assessmentsupporting
confidence: 92%
“…Therefore, these two proteins bear no similarity to known allergenic proteins and the preliminary but not conclusive statement is that they do not represent a risk for allergenicity. Our results are similar to the results reported for PMI by Reed et al (54) and are an endorsement for the wide use of the gene for PMI as a selectable marker in plant genetic transformation.…”
Section: Allergenicity Assessmentsupporting
confidence: 92%
“…Helena and Canino required the lower combination of mannose with sucrose (1,25 g/L mannose and 20 g/L sucrose) in comparison with other woody fruit trees to obtain the most effective selection procedure. Moreover, safety assessments were revealed that there is no any adverse effect of the enzyme on mammalian allergenicity and toxicity (Reed et al, 2001). …”
Section: Selection Systems a Critical Stepmentioning
confidence: 99%
“…PMI enzymes occur in a wide range of organisms including prokaryotes and eukaryotes such as bacteria, yeasts, animals, and humans, as well as plants, in which PMI is involved, for example, in glycoprotein synthesis. In MIR604 maize plants expressing PMI, no change in glycoprotein profiles has been observed (see section 4.1.2), indicating no effects of the introduction of PMI on the host plants' protein glycosylation (Reed et al, 2001). At the EFSA GMO Panel's request, the applicant also provided data on the pH-activity profile of PMI-0105, the bacterially produced analogue of the newly expressed PMI enzyme in maize MIR604.…”
Section: Toxicological Assessment Of Expressed Novel Protein In Maizementioning
confidence: 99%